Hierarchical "tube-on-fiber" carbon/mixed-metal selenide nanostructures for high-performance hybrid supercapacitors. Issue 29 (16th July 2019) - Lv, Li-Ping; Zhi, Chuanwei; Gao, Yun; Yin, Xiaojie; Hu, Yiyang; Crespy, Daniel; Wang, Yong
Abstract : Hierarchical "tube-on-fiber" carbon/mixed-metal selenide nanostructures (Co–Zn–Se@CNTs–CNFs) are constructed and exhibit high performance for hybrid supercapacitors. Abstract : This work reports hierarchical "tube-on-fiber" nanostructures, composed of carbon nanotubes (CNTs) on carbon nanofibers (CNFs), impregnated with mixed-metal selenide nanoparticles (Co–Zn–Se@CNTs–CNFs), as high performance supercapacitors. Co–Zn hybrid zeolitic imidazolate framework-67 (Co–Zn ZIF-67) was electrospun with polyacrylonitrile (PAN) to form nanofibers that were sequentially thermally treated and subjected to selenylation. The "tube-on-fiber" structure is designed to confine the Co–Zn mixed-metal selenide nanoparticles and prevents their agglomeration. Extruded CNTs rooting in carbon nanofibers further improve the electronic conductivity. The mixed-metal selenide allows more accommodation space and faradic reactions compared to single metal selenide. Based on these merits, the hierarchical Co–Zn–Se@CNTs–CNFs exhibit a high specific capacity of 1040.1 C g −1 (1891 F g −1 ) at 1 A g −1 with impressive rate performance in supercapacitors. Furthermore, a hybrid supercapacitor with Co–Zn–Se@CNTs–CNFs as the cathode and porous carbon nanofibers as the anode (denoted as Co–Zn–Se@CNTs–CNFs//PCNFs) is fabricated. It delivers a superior energy and power density of 61.4 W h kg −1 and 754.4 W kg −1, respectively, and meanwhile retains 31.7 W h kg −1 of the energy density with 15 421.6 W kg −1 of the working power. In addition, the assembled supercapacitor device displays an excellent capacity retention of 88.6% after 8000 cycles at 5 A g −1 .